The paradigm of the digital society: synthesis of technocratic and socio-humanitarian approaches - Sholpan Jamanbalayeva; Elena Burova; Ayazhan Sagikyzy; Dinara Zhanabayeva; Alyona Adamidi (Cogent Social Sciences)
Digitization is a global trend that influences the identification of modern states, societies and individuals. The digital civilization sets new development conditions for contemporary states. The aim of this research is to present the paradigm of forming a digital society in Kazakhstan, which is in a state of catching-up modernization, requiring consideration of numerous factors. The methodology of comparability of states, vectors, principles and approaches, as well as the goals of the digital transformation concept (developed for the years 2023–2029), Information and Communication Technology and cybersecurity development, and a comparative analysis of digitalization statistical data have been applied. The article employs a triangulation method: it analyzes data from an international digital readiness index study, examines and visualizes national statistical data and digitalization program indicators and presents the results of a sociological study on societal digitalization conducted by the authors. A SWOT analysis of the conditions, contradictions, risks and opportunities for Kazakhstan has presented the concept of the digital society paradigm. Comparative discourse analysis of disciplinary approaches to the study of digitalization leads to the conclusion of the necessity of the digital society paradigm in the context of comparability of technocratic and humanitarian understanding and critical analysis of the achievements, opportunities and risks of societal digital transformation.